A Framed Field Experiment on Collective Enforcement Mechanisms with Ethiopian Farmers - Reichhuber, Anke; Camacho, Eva; Requate, Till (2012)
We present the results of a framed field experiment with Ethiopian farmers that use the mountain rain forest as a common pool resource. Harvesting honey causes damage to the forest, and open access leads to over-harvesting. We test different mechanisms for mitigating excessive harvesting: a collective tax with low and high tax rates, and a tax/subsidy system. We find that the high-tax scheme works best in inducing the desired level of harvesting, while the tax-subsidy scheme may trigger tacit collusion. Via a panel data analysis we further investigate which variables influence the subjects' decisions during the treatments.